2006
DOI: 10.1063/1.2371080
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio potential energy surfaces, bound states, and electronic spectrum of the Ar–SH complex

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…On the other hand, it could be assumed that melatonin treatment prioritises the presence of antioxidant peptides in the colostrum [ 47 ] over other proteins, including IgG, as was confirmed in MEL lambs by the lower levels of IgG and better redox status. According to previous studies, a decrease in IgG was shown three days after melatonin injection in lactating cows, with a concomitant decrease in somatic cell count in milk of cows [ 58 , 59 ] and ewes’ milk [ 60 ]. Contrary to the latter study and to the present one, others found a higher amount of IgG but no higher amounts of proteins in colostrum just after parturition in melatonin-treated ewes that lambed males compared to females [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it could be assumed that melatonin treatment prioritises the presence of antioxidant peptides in the colostrum [ 47 ] over other proteins, including IgG, as was confirmed in MEL lambs by the lower levels of IgG and better redox status. According to previous studies, a decrease in IgG was shown three days after melatonin injection in lactating cows, with a concomitant decrease in somatic cell count in milk of cows [ 58 , 59 ] and ewes’ milk [ 60 ]. Contrary to the latter study and to the present one, others found a higher amount of IgG but no higher amounts of proteins in colostrum just after parturition in melatonin-treated ewes that lambed males compared to females [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…As for RgSH(X) (Rg = Ne, Ar, and Kr) van der Waals complexes, several groups have constructed the related PESs for the spectroscopic data determination. [41][42][43][44][45][46] For instance, Endo and coworkers 41,[43][44][45] constructed 2D ab initio PES for the SH(X 2 P) + Ar system and later improved to 3D PESs by considering the effect of SH vibration on the intermolecular potential surface. The resulting potential can reproduce the previous spectroscopic results without any effective correction terms included like in the 2D PES.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting potential can reproduce the previous spectroscopic results without any effective correction terms included like in the 2D PES. Hirst et al constructed both ab initio PESs of A 2 S +47 and X 2 P states 46 for the Ar-SH van der Waals molecule. The theoretical excitation spectrum, which took into account the resultant transition dipole moment and the calculated lifetimes, showed agreement with the experimental results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combination of the resulting transition dipole moment and the calculated lifetimes led to a good comparison with experimental fluorescence excitation spectrum. 30,31 Although the SH radicals have been well characterized in the above-mentioned fields, collisional quenching especially for the A state is seldom studied. For effective quenching, this short-lived state must require a large amount of colliders even for a single collision.…”
Section: Introductionmentioning
confidence: 99%